2020
DOI: 10.1103/physrevb.102.054442
|View full text |Cite
|
Sign up to set email alerts
|

sd model for local and nonlocal spin dynamics in laser-excited magnetic heterostructures

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…Figure 1(b) displays the laser-induced dynamics of the the spin accumulation (blue) and magnon chemical potential (red). The spin accumulation shows the typical bipolar behavior, in analogy with previous calculations and experimental observations of the generated spin-polarized electrons [35][36][37]40]. The magnon chemical potential shows different behavior, it can be shown that this is related to that the equilibration of the chemical potentials plays a minor role and the magnon chemical potential opposes the dynamics of the magnon temperature.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 1(b) displays the laser-induced dynamics of the the spin accumulation (blue) and magnon chemical potential (red). The spin accumulation shows the typical bipolar behavior, in analogy with previous calculations and experimental observations of the generated spin-polarized electrons [35][36][37]40]. The magnon chemical potential shows different behavior, it can be shown that this is related to that the equilibration of the chemical potentials plays a minor role and the magnon chemical potential opposes the dynamics of the magnon temperature.…”
Section: Resultssupporting
confidence: 82%
“…The main observation is that the rate at which spin-polarized electrons are generated is determined by the demagnetization rate [35]. This can be understood as being a result of electron-magnon scattering, which stems from the s-d interaction that couples local magnetic moments to itinerant spins [21,26,[38][39][40]. Recent experiments support this view and show a direct proportionality between the spin current injected into a neighbouring nonmagnetic layer and the temporal derivative of the magnetization [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…This implies laser-induced demagnetization and spin-current generation share the same microscopic origin. Recent theoretical work supports this view; the s-d interaction, which mediates angular momentum transfer between local magnetic moments and itinerant electrons, is a promising candidate to explain this link between laser-induced demagnetization and spin-current generation [29][30][31]. Literature suggests the temporal profile of the generated spin currents scales differently with the laser-pulse energy depending on the excitation mechanism.…”
mentioning
confidence: 97%
“…We used ∼10 mJ=cm 2 for the switching threshold, therefore, spin-current in the unit of magnetization ÁM generated by GFC was assumed to be proportional to the fluence and roughly calculated to be ∼1 kA=m. Then, the interface quenching criterion is obtained using the following Recently, the theory of ultrafast magnetization dynamics in a metallic heterostructure that considers the non-local spintransport of s electrons owing to the s-d exchange coupling has been developed, 103) as schematically shown in Fig. 10(a).…”
Section: Single-shot Aos Using Spin-valvesmentioning
confidence: 99%
“…In this model, the s-and d-electron spins are considered within the spin chemical potential s and as a localized magnetization m d . The equations of motion for s and m d are as follows: 103)…”
Section: Single-shot Aos Using Spin-valvesmentioning
confidence: 99%